Upaya Pemerintah Desa Dalam Meningkatkan Motivasi dan Partisipasi Masyarakat Dalam Pembangunan di Desa Fluk Kecamatan Obi Selatan Kabupaten Halmahera Selatan - Rinara Bobi; Abdul Wahid Kamma; Ilfan Baharuddin (Peneliti.net, 2023)
The village is the spearhead of development so it needs to be developed, by increasing community participation because successful development will be the pleasure of the community. The purpose of this study was to find out: Village Government Efforts to Increase Community Motivation and Participation in Development in Fluk Village, South Obi District, South Halmahera Regency and Factors Influencing Village Government Efforts to Increase Community Motivation and Participation in Development in Fluk Village, South Obi District, Halmahera Regency South. This study used descriptive qualitative methods, the number of informants in this study was 15 people. Data collection techniques used observation, interviews and documentation. Data analysis techniques used data reduction, data presentation and conclusions. The results of the study show that: first, community participation in development has not been maximized because the village head as the leader in the village has not been able to establish communication and be transparent with the community so that the community's motivation to participate in every development activity is still low. Second, the constraints for the village government are internal factors: communication, transparency of the village head, external factors: level of education, employment, awareness/willingness.